So you have your polynomial. To factor this out, you need to find the factors of -45 that will add up to 3. These two factors would be -5 and 8. So, you have factored your polynomial! (x-5)(x+8). If you are still unsure, simply use the FOIL method to check and see if you get the same polynomial back. Hope this helps!
Answer:
15
Step-by-step explanation:
Answer: el último
Step-by-step explanation:
Answer:
36
Step-by-step explanation:
u need 12 to make 4 bracelets
4 bracelets x 3 = 12 bracelets
12 beads x 3 = 36 beads
Combine the terms. Note that: one positive and one negative sign results in a negative sign.
Simplify: 5 + (-4) = 5 - 4 = 1
1 + (-7) = 1 - 7 = -6
-6 + 2 = -4
-4 is your answer
~